2021
DOI: 10.3389/fpsyg.2021.674675
|View full text |Cite
|
Sign up to set email alerts
|

“Come on! He Has Never Cooked in His Life!” New Alternative Masculinities Putting Everything in Its Place

Abstract: Communicative acts of some women are perpetuating the dominance that DTM (Dominant Traditional Masculinities) have over both women and OTM (Oppressed Traditional Masculinities). Some women use language in a disdainful manner to reprimand oppressed men’s behavior in daily life situations, the same behavior that such women would not reproach to DTM. But NAM (New Alternative Masculinities) are reacting to this. This article analyzes the communicative acts employed in all these situations, both those produced by w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
(67 reference statements)
1
3
0
Order By: Relevance
“…Through the use of this concept, according to participants, those attitudes of non-dominant men which do not include violence are categorized as sexist, while men who perpetrate violence against women do not receive such criticism. This is in line with previous studies that pointed out this kind of criticism towards men with an oppressed masculinity but not towards men with violent features [ 35 ]. Related to the theory of micromachismo , the participants in this study explained how it implies that all men are the same, while the scientific literature has shown that this is not so [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…Through the use of this concept, according to participants, those attitudes of non-dominant men which do not include violence are categorized as sexist, while men who perpetrate violence against women do not receive such criticism. This is in line with previous studies that pointed out this kind of criticism towards men with an oppressed masculinity but not towards men with violent features [ 35 ]. Related to the theory of micromachismo , the participants in this study explained how it implies that all men are the same, while the scientific literature has shown that this is not so [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this regard, the role of boys in preventing adolescent dating violence has been emphasized in community-based intervention programs to improve adolescents’ health and wellbeing [ 23 ]. Other studies have differentiated between three different types of masculinity to understand the role of men in gender violence: dominant traditional masculinities (DTM), oppressed traditional masculinities (OTM), and new alternative masculinities (NAM) [ 24 , 25 , 26 , 27 ]. DTM represent inegalitarian, dominant, and violent attitudes of men that can lead to gender violence, but that at the same time are associated with attractiveness in the dominant coercive discourse socially transmitted.…”
Section: Introductionmentioning
confidence: 99%
“…A potential explanation can be found in the existing coercive discourse that promotes violence as more attractive and equality as less attractive (Racionero-Plaza et al, 2020;Torras-Gómez et al, 2019). Indeed, research has shown that the presence of the coercive discourse Racionero-Plaza, et al, 2020) socializes many individuals in the attractiveness towards violent masculinity models (Castro & Mara, 2014;Díez-Palomar et al, 2014;Flecha et al, 2013;Joanpere et al, 2021;Ruiz-Eugenio et al, 2021;Valls-Carol et al, 2021, Torras-Gómez et al, 2019. Indeed, research has shown that the presence of the coercive discourse Racionero-Plaza, et al, 2020) socializes many individuals in the attractiveness towards violent masculinity models (Castro & Mara, 2014;Díez-Palomar et al, 2014;Flecha et al, 2013;Joanpere et al, 2021;Ruiz-Eugenio et al, 2021;Valls-Carol et al, 2021).…”
mentioning
confidence: 99%
“…Indeed, research has shown that the presence of the coercive discourse Racionero-Plaza, et al, 2020) socializes many individuals in the attractiveness towards violent masculinity models (Castro & Mara, 2014;Díez-Palomar et al, 2014;Flecha et al, 2013;Joanpere et al, 2021;Ruiz-Eugenio et al, 2021;Valls-Carol et al, 2021, Torras-Gómez et al, 2019. Indeed, research has shown that the presence of the coercive discourse Racionero-Plaza, et al, 2020) socializes many individuals in the attractiveness towards violent masculinity models (Castro & Mara, 2014;Díez-Palomar et al, 2014;Flecha et al, 2013;Joanpere et al, 2021;Ruiz-Eugenio et al, 2021;Valls-Carol et al, 2021). However, no research has explored the audience's perception of James Bond's attractiveness following the changes in the character.…”
mentioning
confidence: 99%